2009
DOI: 10.2478/v10011-008-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-Associated Biochemical Alterations in a Patient with Chronic Neurotoxicity

Abstract: Kratak sadr`aj: Primena metotreksata (MTX) u viso kim dozama i/ili intratekalno u terapiji malignih obo ljenja poput akutne limfoblasti~ne leukemije (ALL) povezana je sa pojavom blagih ili te{kih oblika neuro toksi~nosti. Patogeneza neurotoksi~nosti nije u potpu nosti razja{njena, ali se va`na uloga pripisuje biohe mijskim promenama folatnog i metiltransfernog meta boli~kog puta za koje se smatra da su uzrokovane dejstvom MTX. Opisujemo slu~aj odrasle pacijen tkinje na terapiji recidiva ALL sa simptomima hroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…Signi ficant elevation in the activity of brush border enzymes AAP and GGT was recorded only on day 8 of gentamicin application in examinées of the gentamicin-tre a ted group comparing to the corresponding control (Figure 1 and 2). However, the results of our previous studies showed increased activities of the above two enzymes already on day 2 of gentamicin therapy in the group of 3-5 years old children (11,21). The data of the present study corroborates these results demonstrating that gentamicin acts by injuring the cell mem branes of proximal tubule epithelial cells in neonates, leading to increased enzymatic activities of urinary AAP and GGT localized in these membranes.…”
Section: Discussionsupporting
confidence: 82%
“…Signi ficant elevation in the activity of brush border enzymes AAP and GGT was recorded only on day 8 of gentamicin application in examinées of the gentamicin-tre a ted group comparing to the corresponding control (Figure 1 and 2). However, the results of our previous studies showed increased activities of the above two enzymes already on day 2 of gentamicin therapy in the group of 3-5 years old children (11,21). The data of the present study corroborates these results demonstrating that gentamicin acts by injuring the cell mem branes of proximal tubule epithelial cells in neonates, leading to increased enzymatic activities of urinary AAP and GGT localized in these membranes.…”
Section: Discussionsupporting
confidence: 82%
“…For nephro logists, antibodies to anti-C1q and to nucleosomes are of particular inte rest. It is suggested that complexes of nucleo somes and the resulting antinucleosome antibodies bind to heparan sulphate-rich glomerular structures and induce the inflammatory reactions leading to glo merulonephritis (13,14).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%